2019
DOI: 10.1038/s41388-019-0911-6
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 suppresses human papillomavirus-associated head and neck cancer through antigen-specific CD8+ T-cell responses by upregulating MHC-I expression

Abstract: Evasion of the host immune responses is critical for both persistent human papillomavirus (HPV) infection and associated cancer progression. We have previously shown that expression of the homeostatic chemokine CXCL14 is significantly downregulated by the HPV oncoprotein E7 during cancer progression. Restoration of CXCL14 expression in HPV-positive head and neck cancer (HNC) cells dramatically suppresses tumor growth and increases survival through an immunedependent mechanism in mice. Although CXCL14 recruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 61 publications
3
55
0
Order By: Relevance
“…Suppression of tumor growth and metastasis by CXCL14 is abolished when NK cells are depleted in mice with melanoma, 34 suggesting that the NK cell activity enhanced by CXCL14 is key for tumor suppression in melanoma. Our studies have also shown that NK cells are recruited by re‐expression of CXCL14 in HPV‐positive HNC cells, and NK cell depletion reverted CXCL14‐mediated tumor suppression 12,62 . In addition, our immunocompetent syngeneic HNC model has revealed that CXCL14 re‐expression also induces chemotaxis of CD4 + and CD8 + T cells.…”
Section: Molecular Functions Of Cxcl14supporting
confidence: 60%
See 3 more Smart Citations
“…Suppression of tumor growth and metastasis by CXCL14 is abolished when NK cells are depleted in mice with melanoma, 34 suggesting that the NK cell activity enhanced by CXCL14 is key for tumor suppression in melanoma. Our studies have also shown that NK cells are recruited by re‐expression of CXCL14 in HPV‐positive HNC cells, and NK cell depletion reverted CXCL14‐mediated tumor suppression 12,62 . In addition, our immunocompetent syngeneic HNC model has revealed that CXCL14 re‐expression also induces chemotaxis of CD4 + and CD8 + T cells.…”
Section: Molecular Functions Of Cxcl14supporting
confidence: 60%
“…In addition, our immunocompetent syngeneic HNC model has revealed that CXCL14 re‐expression also induces chemotaxis of CD4 + and CD8 + T cells. While the depletion of CD4 + T cells shows minimal effects, all mice with a compromised CD8 + T cell repertoire grow tumors, indicating that CXCL14‐mediated tumor suppression is reliant on CD8 + T cells 62 . Further contributing to tumor suppression, we have discovered that CXCL14 increases major histocompatibility complex class I (MHC‐I) expression on the tumor cell surface and activates antigen‐specific CD8 + T cells to kill HPV‐positive HNC cells 62 .…”
Section: Molecular Functions Of Cxcl14mentioning
confidence: 98%
See 2 more Smart Citations
“…This impaired HLA class I expression could in most publications be reversed by treatment with respective inhibitors or by IFN-γ [ 56 ]. Furthermore, a link between the expression of the chemokine CXCL14 and HLA class I expression was recently shown [ 57 ], demonstrating the ability of CXCL14 to restore the deficient HLA class I expression in HPV + HNSCC cells. Regarding HLA class II expression, only a minority of HNSCC lesions, but a high frequency of stromal cells expressed HLA class II antigens with higher levels in HPV + compared to HPV - tumors [ 58 ].…”
Section: The Role Of Classical and Non-classical Hla Class I Antimentioning
confidence: 99%